Proposing a Paradigmatic Model of Organizational Culture in Iraqi Schools - Mazloum Al-Jawda, Aziz Abdullah; Jabbari, Negin; Mohammed Ibrahim Al-Suwaidi, Thaer Mohammed Ali; Ghashghaeizadeh, Nasrolah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The objective of the present study is to propose a localized model of organizational culture in the schools of Wasit County, Iraq, emphasizing the identification of cultural dimensions and components relevant to these schools.Methodology:  The research methodology is qualitative, applied in terms of purpose, and exploratory in terms of data type. The statistical population for the qualitative section of the study consists of 30 educational experts and school administrators from Wasit County, Iraq. These individuals were selected as the target population due to their profound experience and knowledge in organizational culture and educational management. Purposeful sampling was employed to select 30 participants from this expert community. Data collection was conducted through semi-structured interviews in the qualitative phase, and data analysis was carried out using Maxqda software.Findings:  The findings indicate that organizational culture in the schools of Wasit County encompasses multiple dimensions, the most significant of which include "educational values," "organizational cohesion and interactions," "commitment and responsibility," and "educational leadership." Ultimately, based on the findings, a paradigmatic model was developed grounded in the Strauss and Corbin model. It can be concluded that the organizational culture in Iraqi schools requires several components to enhance and promote its development.Conclusion:  Therefore, planners can utilize the findings of this study to design organizational culture programs for schools, enabling a deeper understanding of organizational culture.